TINJAUAN TENTANG KEABSAHAN PERKAWINAN TANPA WALI NASAB MENURUT KOMPILASI HUKUM ISLAM (KHI) - Fitcanisa, Jenny Divia; Firdaus, Firdaus; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Provisions regarding marriage guardians are based on the provisions of each religion and the beliefs of those who carry out the marriage. This is in accordance with Article 2 Paragraph (1) of Law Number 1 of 1974 concerning Marriage which states that a marriage is legal if carried out according to the law of each religion and belief. Whereas in Islamic law, guardians in marriage are